(untitled) (African Journal of Biomedical Research, 2023)
Inula glomerata Oliv. & Hiern and Salacia kraussii (Harv.) Harv are medicinal plants used by traditional healers in remote areas of Mbazwana, Northern Kwazulu-Natal, South Africa for ameliorating male sexual disorders including erectile dysfunction (ED), low sperm count and early ejaculation. The study aimed at determining the ameliorative effect of the methanolic crude extracts of Inula glomerata (I. glomerata) and Salacia kraussii (S. kraussii) on butanol-induced erectile dysfunction in Sprague Dawley rats. The crude extract was prepared by maceration using methanol. Animal study was conducted whereby thirty-five male Sprague Dawley rats were divided into seven experimental groups: normal group, n-but (10 mg/kg), n-but+ Ig (50 and 250 mg/kg), n-but+ Sk (50 and 250 mg/kg) and n-but+ Cialis (5mg/kg). The experiment lasted for 28 days, after which various biochemical assays (acetylcholinesterase, ACE, arginase, testosterone, and uric acid) was done. The cytotoxicity of the crude extracts was also determined. The results revealed that n-butanol induced erectile dysfunction in the rats by decreasing mounting frequency, testosterone and nitric oxide level and simultaneously elevated the activities of arginase and acetylcholinesterase. The plants however, inhibited arginase and acetylcholinesterase when compared to the untreated. Furthermore, the plants’ extracts were able to increase the level of testosterone and nitric oxide. It can be inferred that both plants could be promising natural therapy for erectile dysfunction. Nonetheless, the plants’ extracts are toxic hence should be taken with caution.